Health Care Workers And Patients Safety In Nursing Homes - Sepp, J.; Reinhold, K.; Järvis, M.; Tint, P. (European Scientific Journal, ESJ, 2016)
The aim of the study was to review the literature in the area of health care of nursing homes using meta-analysis and to develop a framework for improvement of patients and caregivers safety. The method used: a literature search conducting databases EBSCOhost, Academic Search Complete, Business Source Complete, Health Source – Consumer Edition, Health Source: Nursing/Academic Edition and Retrieval System Online. The key words in the internet search were “safety climate in health care” and “worker and patient safety”. Limitations were English language, full text, human, the years 2006-2015. We eliminated studies that were specific to industry, military, aviation, disease, medical speciality, technologies, or hospital departments/units. As a result, the literature overview was achieved that provides the sources for a good care and enables the patient safety; from the caregivers side we need the workers who are committed to provide a good care and are non-punitive and do can organize the blame-free environment in the nursing homes. The good safety culture in nursing homes is achieved if the workers are able to speak freely about accidents and eager to learn from errors, mistakes and hazards. The authors of the current paper have created a model showing the main components of safety climate which help to provide a good care and ensure patients and workers safety in the nursing homes.